Identifying priority value chains in Ghana - Hartley, Faaiqa; Arndt, Channing (International Food Policy Research Institute, 2018)
This working paper identifies agricultural activities and value chains in Ghana whose expansion is most effective at generating economic growth, reducing national and rural poverty, creating jobs, and improving nutrition by diversifying diets. The Rural Investment and Policy Analysis (RIAPA) model of the Ghanaian economy is used to estimate how increasing production in different agricultural sectors leads to changes in national and household outcomes.1 RIAPA captures linkages between sectors and rural-urban economies, as well as changes throughout the agriculture-food system (AFS).